(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2025)
The behaviour of black holes is one of the most challenging problems facing cosmologists. It was thought that the behaviour of black holes can be described by quantum laws. In this model, using Schrödinger equation and the ordinary gravitational field equation for spherical bodies, a new quantum gravity equation was proposed to describe the behaviour of the black holes. Assuming that the universe undergo a phase transition to become a black hole or if the solar system is trapped by a black hole, the time evolution will certainly be different from that of our ordinary solar system. This work proves that the distance traversed by the moon in one day inside the black hole is equal to that traversed by the moon in 1000 year.